2021
DOI: 10.1002/agj2.20685
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nitrogen diagnosis methods in sunflower

Abstract: Nitrogen deficiency can severely limit sunflower (Helianthus annuus L.) grain yield and quality. Our objective was to evaluate N diagnosis methods based on: (a) preplant soil nitrate-nitrogen (NO 3 --N) test (PPSNT) and soil N mineralized in shortterm anaerobic incubation (Nan), (b) Greenness index (G I ) and the normalized difference vegetation index (NDVI) measured at 6 (V 6 ) and 12 (V 12 ) leaves, and (c) grain nitrogen concentration (N c ). Seventeen experiments were carried out between 2010 and 2019 in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
2
1
Order By: Relevance
“…Hernandez et al, 2021). As an example, Nan values in our study (∼60 mg kg −1 ) were greater than those observed byDiovisalvi et al (2018) (∼50 mg kg −1 ).…”
contrasting
confidence: 64%
See 2 more Smart Citations
“…Hernandez et al, 2021). As an example, Nan values in our study (∼60 mg kg −1 ) were greater than those observed byDiovisalvi et al (2018) (∼50 mg kg −1 ).…”
contrasting
confidence: 64%
“…Along this line, at similar edaphoclimatic conditions, Tovar Hernandez et al. (2021) observed that the initial N availability (N–NO 3 − ) and N mineralization throughout the growing season were the variables that defined sunflower grain response to N. The observed yield response was lower than that reported by other authors (540–1400 kg ha −1 ) (Diovisalvi et al., 2018; Schultz et al., 2018; Wajid et al., 2012), which can be attributed to differences in the soil potentially mineralizable N between studies (Tovar Hernandez et al., 2021). As an example, Nan values in our study (∼60 mg kg −1 ) were greater than those observed by Diovisalvi et al.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation